The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.1177/193229680800200407
|View full text |Cite
|
Sign up to set email alerts
|

Skin Advanced Glycation End Product Accumulation is Poorly Reflected by Glycemic Control in Type 2 Diabetic Patients (ZODIAC-9)

Abstract: Background: Glycemic memory can be reflected by tissue accumulation of advanced glycation end products (AGEs). In type 1 diabetes mellitus (T1DM) patients, hemoglobin A1c (HbA1c) levels over various time periods poorly predicted the accumulation of different AGEs in skin biopsies. Our aim was to investigate whether HbA1c assessments can predict the change in skin AGEs during time in type 2 diabetes mellitus (T2DM). Methods: We included 452 T2DM patients participating in a shared-care setting, who are screened … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
25
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(31 citation statements)
references
References 15 publications
6
25
0
Order By: Relevance
“…Specifically, HbA 1c , blood pressure and lipid profile did not contribute. Earlier studies showed that HbA 1c and skin autofluorescence have a limited relation [14], suggesting that skin autofluorescence is only partly determined by the components of the slow Maillard reaction.…”
Section: Discussionsupporting
confidence: 72%
“…Specifically, HbA 1c , blood pressure and lipid profile did not contribute. Earlier studies showed that HbA 1c and skin autofluorescence have a limited relation [14], suggesting that skin autofluorescence is only partly determined by the components of the slow Maillard reaction.…”
Section: Discussionsupporting
confidence: 72%
“…These findings suggest that a reduction in AGEs is one of the indexes of restrain in diabetes complications (3,16,17). After a mean follow-up duration of 3.3 years, Gerrits et al (18) reported that integrated HbA 1c poorly predicts changes in skin AGEs as measured with skin AF in patients with type 2 diabetes.…”
Section: Resultsmentioning
confidence: 99%
“…Such association was not found in T2DM in a cohort by Gerrits et al [30]. Since the relatively short turnover time of hemoglobin [31] as compared to skin AGEs formation and degradation, the HbA 1c values cannot always reflect AGEs accumulation.…”
Section: Discussionmentioning
confidence: 97%